Semantic Characteristics of the Emerging Popular Construction "Cloud X" in Modern Chinese Language - Luo, Yingyu (Transactions on Social Science, Education and Humanities Research, 2024)
Accompanied by the development of the Internet and big data, "cloud X" has become a popular construction that is more frequently used in the Internet in recent years. Studying and analyzing the generation mechanism and evolution process of "Cloud X" is of great reference significance for understanding the development of popular words in the new period and the word formation process of popular words. Therefore, this paper analyzes the popular word "cloud X" from the semantic perspective, taking the semantic evolution of "Yun (cloud)" as the entry point. In the process of exploring "Yun (cloud)", this paper will focus on the transformation of the semantic features of "Yun (cloud)", observing the original meaning of "Yun (cloud)",Yun (cloud)" in "cloud computing", and the semantic features of "Yun (cloud)" after "cloud X" has become a construction. By examining the similarities and differences of the semantic features, we can explore the process of "Yun (cloud)" gradually changing from a real word to a class of affixes and the reasons for the change.